Penerapan Metode Demonstrasi Terhadap Peningkatan Hasil Belajar Peserta Didik Kelas XI MIA 2 Pada Mata Pelajaran PPKn Di SMA Negeri 2 Rantau Utara - Ginting, Melly Andriani Br (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the improvement of learning outcomes by using a differentiated approach in class XI Mia 2 of SMA Negeri 2 Rantau Utara. This research is a Classroom Action Research (CAR) conducted in class XI Mia 2 of SMA Negeri 2 Rantau Utara. The subjects of this study are all the students in class XI Mia 2, totaling 36 students. The data collection techniques used are indirect communication and observation. The analysis technique used is descriptive quantitative. The results of this study indicate that in cycle I, by applying the demonstration method, the average class score was 74.7 with a percentage of 63.8%. This shows that the average has not yet reached the standard completion criteria. This improvement has not reached the classical completion criteria of 80%. In cycle II, by applying the demonstration method and improvements from cycle I, the average class score was 83.7 with a classical completion percentage of 88.8%. Thus, the action hypothesis formulated in this study can be accepted.